Development and Validation of a Self-directed Learning Scale for Pre-Service Science and Technology Teacher - Wahyudi; Agus Setiawan; Andi Suhandi; Achmad Samsudin (Jurnal Penelitian Pendidikan IPA, 2025)
The ability of prospective science and technology teachers to engage in Self-Directed Learning (S-DL) is essential for their professional growth in an evolving educational landscape. However, existing instruments to assess S-DL readiness often lack comprehensive validation. This study aims to develop and validate an instrument to measure S-DL readiness among prospective science and technology teachers. The research followed a structured process, including instrument design, expert validation, pilot testing, and psychometric evaluation. A sample of 100 students participated in the validation process, ensuring the instrument's reliability and validity. Content validation was conducted with expert judgment, while statistical analyses, including factor analysis, were used to assess construct validity. The final instrument consists of 42 items, demonstrating strong validity and reliability. These findings confirm that the developed S-DL instrument is an effective tool for measuring students' readiness for self-directed learning. The results provide valuable insights for improving teacher education programs by integrating self-directed learning strategies and supporting further research in this field.